Efeitos metabólicos e comportamentais da privação de sono associada ou não ao exercício físico - Silva, Bruna Rafaele Diógenes da (2020)
Objective: To evaluate the effects of exercise, sleep deprivation (SD) and exercise associated with SD, on memory, anxiety and depression behaviors, and on lipid and glycidic metabolites through serum, liver and muscle levels of glucose, lactate, glycogen, cholesterol and triglycerides. Metabolic patterns in the cerebral cortex and hippocampus were studied. Methods: Mice (N = 48) were randomly allocated into 4 groups (N=12 each): control (C), exercise (EX), sleep deprivation (SD) and sleep deprivation followed by exercise (EXSD). The animals were trained (8 weeks) on treadmill (9cm/s) from 10:00 to 12:00. The SD (72h) was obtained by the modified multiple platform technique (Porsolt). Blood levels of glucose, lactate, cholesterol (total and fractions) and triglycerides were evaluated. Behavioral tests included forced swimming, Y-Maze and elevated cross maze and were performed (before and after 24h of the experiment). Blood, liver and muscle samples were collected to determine glycogen, cholesterol and triglycerides. Samples of cerebral cortex and hippocampus were analyzed by liquid chromatography / mass spectrometry. Results: The exercised animals (EX) presented higher blood levels of glucose, lactate and triglycerides. Blood cholesterol levels remained unchanged in all groups. Blood triglycerides were reduced in PS and EXSD groups. The EX group had higher liver glycogen levels and a modest increase in muscle. Hepatic cholesterol and triglycerides were markedly reduced in the SD group and this was reversed in previous exercise animals (EXSD). EXSD animals showed improvement in memory test when compared to SD group (Y-maze). Chemometric analysis revealed a distinct metabolic profile between the SD, EXSD, EX and C groups. Exercise increased the levels of lactate, n-acetylaspartic acid, creatine and taurine while there was a reduction in the content of ethanol, alanine, gamma-aminobutyric acid ( GABA), myo-inositol, choline and acetate. SD increased acetate and reduced ethanol, lactate, alanine, GABA, n-acetyl aspartic acid, creatine, choline, taurine and myo-inositol in the cortex. SD increased acetate levels and reduced ethanol, lactate, alanine, GABA, n-acetyl aspartic acid, creatine, choline, taurine and myo-inositol in the cortex. The cortex of group C and EXSD animals presented similar composition. Conclusion: Chronic aerobic exercise and PS modify metabolic and behavioral parameters in mice. Prior exercise improved memory in animals undergoing SD. Importantly, the deleterious reduction in hepatic cholesterol and triglycerides associated with SD was reversed by exercise (EXSD), suggesting that the effects of exercise are modulated by pre-existing conditions. Prior 11 exercise (EXSD) reversed changes in cerebral cortex in animals undergoing SD. Therefore, previous exercise reversed the changes induced by SD and showed a protective action, recovering the hepatic lipid reserves and metabolites in the cerebral cortex.